PENGEMBANGAN POTENSI PARIWISATA RELIGI (STUDI KASUS PADA MAKAM SYEKH ABDURRAHMAN SIDDIQ DI DESA TELUK DALAM KECAMATAN KUALA INDRAGIRI KABUPATEN INDRAGIRI HILIR) - Ali Azhar Ali Azhar; Bayu Fajar Susanto; Mulono Aprianto (Jurnal Indragiri Penelitian Multidisiplin, 2021)
This study aims to describe the potential development of religious tourism at the tomb of Sheikh Abdurrahman Siddiq in Teluk Dalam Village, Kuala Indragiri District, Indragiri Hilir Regency, including the process of forming tourism objects, developing tourism objects, and the impact of their development. This research is a qualitative type with a case study strategy. Data collection techniques by observation, interviews, and documentation. Test the validity of the data by triangulation of data sources and data collection techniques. Analysis of the data using interactive techniques. This study shows that the formation of this tourist attraction stems from the collapse of the Indragiri kingdom. Sheikh Abdurrahman Siddiq, a Mufhti of the Indragiri Kingdom, built a mosque as a means of spreading Islam in the Hidayat area. After he died, he was buried in Teluk Dalam village in the courtyard of the mosque that was built. The tomb is sacred by the community and used as a religious tourism object. Many people visit for pilgrimage. For this reason, development is carried out, including the addition of tourist objects such as the Sheikh Abdurrahman Siddiq Museum and the Mosque to make it more comfortable. In addition, the addition of basic facilities in the form of an entrance gate and a roof to protect the tomb. Complementary facilities are in the form of pilgrim rules and mosques. Supporting facilities include parking lots, canteens, and clothing stores. However, there are several facilities that have not been developed optimally, namely repairing basic facilities in the form of repairing entrances to tombs and mosques. Improvement of complementary facilities in the form of ablution places and toilets. The development of tourist information includes introducing tourism objects to outsiders and to increase tourist visits. This can be done by using brochures, accessing google internet services. This development has a positive impact on the local economy. It can be seen from the growth of various business fields, such as clothing stores, food stalls, street vendors, and entertainment.